Keanekaragaman Makrozoobentos sebagai Bioindikator Lingkungan di Sungai Lantahiwo Desa Kotawo Kecamatan Kulisusu Barat Kabupaten Buton Utara - La Baco Sudia; Kahirun Kahirun; La Ode Muhammad Erif; Abdul Manan; Surya Cipta Ramadhan Kete; Ruslin Ruslin (University of Halu Oleo, 2023)
Macrozoobentos are animals that live permanently in sediments at the bottom of the water, both on soft and hard substrate conditions. Macrozoobenthos contribute greatly to the function of aquatic ecosystems and play important roles such as mineralization processes in sediments and organic material cycles and play a role in transferring energy through the food chain. Based on the results of research conducted on the Lantahiwo River, Kotawo Village, West Kulisusu District, the species richness of macrozoobenthos found in the Lantahiwo River was varied where the number of individuals obtained from station 1 (upstream) was 20 individuals. At station 2 (middle of the river) there were 60 individuals, while at station 3 (downstream) there were 14 individuals. The river is a form of aquatic ecosystem that has an important role in the hydrological cycle and functions as a catchment area for the surrounding area. So that the condition of a river is strongly influenced by the characteristics of the surrounding environment. The sampling point includes looking at the considerations made in the field and sampling at stations 1, 2 and 3 is carried out in stages, first in the upstream, middle and downstream parts of the river then observations are made with several parameters that are considered important by researchers as key parameters that represent and describes the waters of the Lantahiwo River. This research was conducted from March to April 2020 in Kotawo Village, Kulisusu Barat District, North Buton Regency. Based on the results of identification, where the types of macrozoobenthos found in the Lantahiwo River at stations 1 to 3 consist of 2 families and 2 classes, namely; types of family Gerridae from class Bivalvia, species from family Thiaridae from class Gastropods, species from family Thiaridae from class Macrozoobentos were found at each station.